Annulated Radical Cations with a C4E2‐Core (E = P, As, Sb): Stable Pnictogen Analogs of Elusive Aryl Radical Anions of Birch Reduction Reactions - Steffenfauseweh, Henric; Vishnevskiy, Yury V.; Neumann, Beate; Stammler, Hans‐Georg; Snabilié, Demi D.; Bruin, Bas; Ghadwal, Rajendra S. (Angewandte Chemie International Edition, 2025)
The benzene radical anion (C6H6)●−, possessing a 7π‐electron count, is a crucial intermediate in the Birch reduction and has been extensively studied both experimentally and theoretically. Herein, we report the tricyclic pnictogen radical cations [(ADC)E]2[B], [2‐E][B] (ADC = PhC{N(Dipp)C}2; Dipp = 2,6‐iPr2C6H3; E = P, As, Sb; [B] = [B1] = B(C6F5)4 or [B2] = {3,5‐(CF3)2C6H3}) featuring a central 7π‐electron planar C4E2 ring embedded between two 1,3‐imidazole‐based anionic dicarbene (ADC) frameworks, as crystalline solids. [2‐E][B] are prepared by one‐electron (1e) oxidations of the corresponding base‐stabilized cyclic bis‐pnictinidene compounds [(ADC)E]2 (1‐E). Calculated spin densities (for E = P 76%, As 80%, Sb 88%) and EPR measurements suggest that [2‐E]●+ are pnictogen‐centered radicals and stabilized by the delocalization of the unpaired electron over the C4E2 ring. The EPR spectra of [2‐E][B] exhibit characteristic signals for S = ½ systems with clear hyperfine coupling constants for the two similar P, As, or Sb nuclei. Further 1e‐oxidations of [2‐E][B] result in the dicationic 6π‐electron C4E2‐species [(ADC)E]2[B]2 [3‐E][B]2, which readily undergo comproportionations with 1‐E to afford [2‐E][B]. The radical reactivity of [2‐E][B2] is shown with 2,2,6,6‐tetramethylpiperidinyloxyl (TEMPO) and diphenyl diselenide (PhSeSePh) in yielding compounds [(ADC)2E{E(TEMPO)}][B2] (4‐E) (E = P, Sb) and [(ADC)2P{P(SePh)}][B2] (5‐P), respectively. One‐electron (1e‐) oxidations of the base‐stabilized cyclic bis‐pnictinidene compounds 1‐E afford the 7π‐electron C4E2‐ring‐containing radical cations [2‐E]●+, which are valence isoelectronic to the benzene radical anion [C6H6]●− of the Birch reduction reactions. Further, 1e‐oxidations of [2‐E]●+ give the dications [3‐E]2+, while reactions with TEMPO (or Ph2Se2) yield the corresponding diamagnetic monocations.